1988
DOI: 10.1037/0022-0663.80.3.337
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' accuracy in evaluating students' self-image: Effect of perceived closeness.

Abstract: This document is copyrighted by the American Psychological Association or one of its allied publishers.This article is intended solely for the personal use of the individual user and is not to be disseminated broadly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 8 publications
0
7
0
1
Order By: Relevance
“…Birch and Ladd (1998) reported that antisocial behavior, defined in terms of aggression and hyperactivity, was positively correlated with child-teacher conflict in kindergarten and first grade. Teachers' interactions with aggressive children have been found to be angry and punishing (Coie & Koeppl, 1990), and lacking in warmth and encouragement (Birch & Ladd, 1998;Itskowitz, Navon, & Strauss, 1988). It is not surprising, then, that aggressive children are less likely than nonaggressive children to have securely attached childteacher relationships .…”
Section: Aggressionmentioning
confidence: 89%
“…Birch and Ladd (1998) reported that antisocial behavior, defined in terms of aggression and hyperactivity, was positively correlated with child-teacher conflict in kindergarten and first grade. Teachers' interactions with aggressive children have been found to be angry and punishing (Coie & Koeppl, 1990), and lacking in warmth and encouragement (Birch & Ladd, 1998;Itskowitz, Navon, & Strauss, 1988). It is not surprising, then, that aggressive children are less likely than nonaggressive children to have securely attached childteacher relationships .…”
Section: Aggressionmentioning
confidence: 89%
“…When pupils have made teachers' jobs difficult for a sustained period of time, the interaction of some teachers with those aggressive pupils has been found to be characterised by resentment and a tendency to anticipate aggressive intention (Coie & Koeppl, 1990), and to be lacking in warmth and encouragement (Birch & Ladd, 1998;Itskowitz, Navon, & Strauss, 1988). When aggressive children do interact with their teachers, the results are often negative (e.g., Alvarez, 2007;Bibou-Nakou, Stogiannidou, & Kiosseoglou, 1999;Poulou & Norwich, 2000).…”
Section: Pupil Aggression and The Teacher-pupil Relationshipmentioning
confidence: 96%
“…They are frequently noted as a significant source of teacher stress (Boyle, Borg, Falzon, & Baglioni, 1995). Teacher interactions with these students tend to be critical and punishing in nature (Coie & Koeppl, 1990), and are often characterized by high conflict and low warmth (Itskowitz, Navon, & Strauss, 1988). Although the punishment following a student's problem behavior may be needed to reduce the likelihood of future bad behavior, the student's repeated exposure to punishment, especially in the absence of positive attention from teachers, is more likely to perpetuate a sense of alienation from teachers and school, which may in turn lead to intensified anger and defiance (Baker, 1999;Van Acker, Grant, & Henry, 1996).…”
mentioning
confidence: 98%